MERANCANG LEMBAGA KEUANGAN MIKRO SYARIAH YANG TEPAT PADA DESA CIBITUNG KULON, KECAMATAN PAMIJAHAN, KABUPATEN BOGOR. - Trihantana, Rully; Mursyidah, Azizah; Dianita, Mia (Jurnal Pengabdian Kepada Masyarakat Perbankan Syariah: Program Studi Perbankan Syariah., 2024)
Economic progress and financial inclusion have an important role in realizing sustainable development and community empowerment. In this context, Islamic microfinance institutions emerge as a promising alternative to encourage local economic growth by integrating Islamic economic principles and financial inclusion. This community service aims to analyze the implementation of sharia microfinance institutions in the Cibitung Kulon village community with a focus on the financial inclusion approach and the resulting economic impact. The subject of this community service is the people of Cibitung Kulon Village/Subdistrict, Pamijahan District, Bogor Regency, West Java Province. In this community service activity is carried out based on a qualitative approach method, data is collected through in-depth interviews with community members and relevant stakeholders, as well as direct field observations. Data analysis was carried out by the method content analysis to understand community perceptions and experiences regarding Islamic microfinance institutions. The result of this community service is a significant increase in financial inclusion in Cibitung Kulon Village through the active participation of the community in Islamic microfinance institutions. Community involvement in local economic activities has been proven to produce positive economic impacts, including increased production and income. A symbiotic relationship between financial inclusion and economic impact has been identified, in which access to sharia microfinance has driven the growth of small and medium scale businesses and community economic empowerment. With this community service, it can be concluded that the implementation of Islamic microfinance institutions in villages is able to encourage broader financial inclusion and produce a positive impact on the local economy. This research provides important insights for policy making in the field of financial inclusion and provides recommendations for the development of more effective and sustainable Islamic microfinance institutions at the village level.